2017
DOI: 10.1111/are.13468
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial community composition and distribution in different segments of the gastrointestinal tract of wild-caught adultPenaeus monodon

Abstract: Bacterial community associated with the gastrointestinal (GI) tract of aquaculture animals can play important roles in health, nutrition and disease. Compared with the GI tract of aquatic vertebrates such as fish, crustacean GI tract has unique structures and surfaces in different segments that may contribute to differences in the bacterial communities. This study examined the bacterial composition and distribution in different segments along the GI tract and in digesta of wild-caught adult Penaeus monodon usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 65 publications
3
11
0
Order By: Relevance
“…Here, bacteria associated with the intestinal tract of black tiger shrimp and bacterial communities in rearing-water in Vietnam were characterized by using the high-throughput 16S rRNA-based Illumina sequencing approach. The result was consistent with the previous reports that Proteobacteria was the predominant phylum associated with the intestine of black tiger shrimp (Mongkol et al, 2017;Rungrassame et al, 2013;. However, little difference exists between shrimp bacteria and water bacteria for the symptomatic pond.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Here, bacteria associated with the intestinal tract of black tiger shrimp and bacterial communities in rearing-water in Vietnam were characterized by using the high-throughput 16S rRNA-based Illumina sequencing approach. The result was consistent with the previous reports that Proteobacteria was the predominant phylum associated with the intestine of black tiger shrimp (Mongkol et al, 2017;Rungrassame et al, 2013;. However, little difference exists between shrimp bacteria and water bacteria for the symptomatic pond.…”
Section: Discussionsupporting
confidence: 93%
“…(Johnson et al, 2008;Cardona et al, 2016). To date, the bacterial communities in commercially important shrimp species have been examined from the culture dependent methods to molecular methods in other regions (Iehata, Deris, Ikhwanuddin, & Wong, 2017;Mongkol et al, 2017;Zheng et al, 2017). However, the bacterial communities in shrimps in Vietnam are poorly understood with few studies have been carried out (Chen, Ng, Wu, Chen, & Wang, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, characterization of microbial establishment www.nature.com/scientificreports www.nature.com/scientificreports/ in their early life stages will be crucial due to their potential benefits to promote healthy gut microbial balance from young stages 22,23 . Our group has initiated efforts to investigate the bacterial community associated with P. monodon under various conditions [7][8][9][10]24 . Here, we present the first report on bacteria associated with early life stages in P. monodon from nauplius to zoea, mysis and postlarvae by using 16S rRNA gene sequencing analysis.…”
Section: Discussionmentioning
confidence: 99%
“…These dominant phyla are known as typical microflora in various aquatic organisms. For instance, Proteobacteria and Bacteroidetes were distributed along the intestines of P. monodon juveniles 8,10,24 , Litopenaeus vannamei [25][26][27][28] and zebrafish Danio rerio 29 . We also identified that Vibrio was the most dominant genus in all shrimp stages, which was congruent with other previous reports that it was commonly associated with various marine organisms 9,31 and marine environment 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Recognizing the importance of microbial biomass and diversity on the health and production of cultured invertebrates, several microbiome studies have analysed the gut microbiome of wild-caught shrimps (Cornejo-Granados et al 2017;Phayungsak et al 2018;Rungrassamee et al 2016) as well as cultured shrimps under different abiotic and biotic factors.…”
Section: Introductionmentioning
confidence: 99%